Self-cleaning engineered cementitious composites. (November 2015) - Zhao, Aiqin; Yang, Jinglei; Yang, En-Hua
Abstract: Engineered cementitious composite (ECC) is a strain hardening cementitious composite with extreme tensile ductility of several percent. Few emerging applications of ECC, including lightweight building façade and pavement, make self-cleaning a desirable functionality to be added into the material. This study aims to impart photocatalytic properties into ECC for engaging self-cleaning. Influence of TiO2 content on mechanical properties, cleaning efficiency, surface wettability, and dirt pick-up resistance of white ECC was studied. It shows that the inclusion of TiO2 in ECC engages photocatalysis, facilitates the decomposition of RhB, and enhances photo-induced hydrophilicity significantly. As a result, TiO2 -ECC possesses self-cleaning with higher dirt pick-up resistance than normal ECC. However, TiO2 photocatalysis may adversely affect the flexural strength and ductility of ECC due to weakened fiber/matrix interface bond after UV/sunlight irradiation.